The Lavrion silver district: Reassessing its ancient mining history. Issue 4 (9th March 2021) - Ross, James; Voudouris, Panagiotis; Melfos, Vasilios; Vaxevanopoulos, Markos; Soukis, Konstantinos; Merigot, Kelly
Abstract: Lavrion was an important silver mining district in the ancient world, exploited almost continuously from the fourth millennium BC. Its mining history is central to understanding the availability of silver, lead and copper in Greece and the Aegean through the Bronze age. This history is also relevant to the phenomenal rise of Athens in the 5th century BC. Our reassessment of the mineralisation and ancient mining history at Lavrion provides a clearer understanding of its capacity to generate wealth and the scale of its impact on Athens. Integration of new geochemical and geological data with existing information has produced outcomes that help address these two issues. Foremost is the contrasting character of mineralisation at the upper 'first' and lower 'third' contacts and their marked differences in silver content, spatial distribution and supergene alteration. Discovery of the concealed, bonanza mineralisation of the third contact at Kamariza, possibly early in the 5th century BC, followed about 3000 years of mining, which appears to have been largely restricted to discontinuous, low‐grade mineralisation at the first contact. Undoubtedly, this later discovery had enduring impacts on Lavrion and Athens, and it most likely funded the trireme fleet, which brought victory over the Persians at Salamis in 480 BC.